Studies on Lophocoleaceae. XXIV. Chiloscyphus alpicola J.J.Engel, an interesting new liverwort species from New Zealand together with nomenclatural changes in Tetracymbaliella Grolle - Engel, John (Phytotaxa, 2015)
Chiloscyphus alpicola J.J.Engel, a new member of the Lophocoleaceae from New Zealand, is described and illustrated and Tetracymbaliella subsimplex (Austin) J.J.Engel, endemic to Tasmanian, is a new combination.